The Effectiveness of Mind Mapping Model and Think Pair Share Aided by Audio Visual Media to Improve Fantasy Story Writing Skill - Fahrudin, Mohammad Khoirul; Haryono, Haryono; Prihatin, Titi (Universitas Negeri Semarang, 2019)
The implementation of the learning model is an important matter to develop students’ skills. Among them is writing – the most difficult skill. Innovation in managing learning management is a solution to improve students’ wiring skill. This research aims to find out the effectiveness of mind mapping and think pair share to improve fantasy story writing skill, to analyze the differences of male and female writing skill, and to analyze the interaction of learning model and sex types of seventh graders of Bulu 02 Primary School, Rembang City. It is a factorial (2x2) experimental research. The sample is taken by proportionate stratified random sampling. The data is analyzed using Two-way ANOVA. The findings show: (1) different effectiveness between mind mapping and think pair share aided by audiovisual media to improve fantasy story writing skill, (2) different learning achievement of male and female toward fantasy story writing skill, (3) no interaction between mind mapping and think pair share aided by audiovisual media to male and female in improving fantasy story writing skill. Based on the findings, it can be concluded: there is a difference of effectiveness of both model; there is a difference of learning achievement between male and female students, but there is no interaction between those two models to sex types of the students. This study contributes to the latest novelty of mind mapping learning model and thinks pair share in learning Indonesian language and contributes scientifically to education by providing innovation in learning the Indonesian language.